The effect of crop density on maize grain yield - Mandić Violeta (Biotechnology in Animal Husbandry, 2016)
The aim of this investigation was to estimate the effects of crop density on the plant height (PH), ear height (EH), leaf number per plant (LN), ear length (EL), number of rows per ear (NRE), number of grain per row (NGR), number of grain per ear (NGE), grain weight per ear (GWE), cob weight (CW), 1000-grain weight (1000-GW), ear diameter (ED) and grain yield (GY) in staygreen maize hybrid Dijamant 6 (FAO maturity group 600). Three crop densities (51020 plants ha-1, 59524 plants ha-1 and 71429 plants ha-1) were tested. The field experiment was carried out during 2006 and 2007 at Srem region (Putinci: latitude 44° 59' 19' N; longitude 19° 58' 11' E). Plots were organized as completely randomized block system design in four replications. PH (284.3 cm), EH (119.9 cm), LN (13.9), EL (20.8 cm), GWE (232.5 g), CW (56.4 g), 1000-GW (378.4 g) and GY (13.56 t ha-1) were significantly higher in 2006 (favorable climatic conditions) than in 2007 (258.5 cm, 112.8 cm, 13.2, 17.9 cm, 192.9 g, 46.9 g, 232.7 g and 11.50 t ha-1, respectively). Increasing crop density significantly increased the PH, EH and GY, and significantly decreases the EL, NGR, NGE, GWE, CW and 100-GW. The crop density of 71429 plants ha-1 is the optimal for growing this hybrid in Srem region. On that crop density hybrid more efficiently used available resources and achieved the highest grain yield.